What determines corporate sukuk issuance in Indonesia? - Abdul Qoyum; Rizka Hendriyani; Siti Nur Azizah; Prasodjo Prasodjo (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
We emporically investigates the determinant of corporate sukuk issuance in Indonesia Islamic capital market. For doing so, we include Indonesia Corporate Sukuk Index (ICSIX),Capital Market Index (IHSG),Company Rating, and Financial Distress as the independent variable of this study. By studying 27 corporate sukuk issued by 17 companies between 2010 and 2018 this study finds that ICSIX and financial distress have a positive significant effect on corporate sukuk issuance. While the rest of variables, IHSG and company rating have a negative significant effect on corporate sukuk issuance.